VENUE LOCATION MATTERS: ITS IMPACT ON MUSIC CONCERT ATTENDANCE AT THE PALEMBANG SPORT AND CONVENTION CENTER - Zahwa Humaira; Wisanggeni Agus Priyanto; Mulkan Setiawan (Politeknik Pariwisata Palembang, 2025)
This study aims to examine the influence of event venue location selection on visitors’ decisions to attend music concert events at the PSCC venue. The research employed a quantitative method with purposive sampling as the sampling technique. A total of 100 respondents were selected as the sample, consisting of visitors who had attended music concert events previously held at the PSCC venue. The sample size was determined based on Likert scale calculations as a representative portion of the population. Data were collected through questionnaires that had been tested for validity and reliability, followed by classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results of the analysis show that the selection of event venue location has an influence of 41.5% on visitors’ decisions to attend music concert events at the PSCC venue.